1993
DOI: 10.3171/jns.1993.79.6.0839
|View full text |Cite
|
Sign up to set email alerts
|

Nondiagnostic CT-guided stereotactic biopsies in a series of 407 cases: influence of CT morphology and operator experience

Abstract: Nondiagnostic biopsies were analyzed in a consecutive series of 407 patients undergoing computerized tomography (CT)-guided stereotactic biopsies. These were categorized as either negative biopsies, when normal tissue or nonspecific pathology was found, or inconclusive, when a definitive diagnosis could not be made although representative tissue was obtained. Nineteen biopsies (4.7%) were negative and 10 (2.4%) were inconclusive, giving an overall nondiagnostic biopsy rate of 7.1% (29 of the 407 cases). Suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 10 publications
0
24
0
9
Order By: Relevance
“…It is a fact that intraoperative bleeding through the biopsy needle seriously increases the surgeon's anxiety and reluctance to proceed with any further biopsy. Ranjan et al (29) found no significant difference between the most experienced and other surgeons regarding negative biopsies. Two non-diagnostic cases were the 94 th and 125 th procedures in the present study.…”
Section: Diagnostic Yield and Accuracymentioning
confidence: 94%
See 1 more Smart Citation
“…It is a fact that intraoperative bleeding through the biopsy needle seriously increases the surgeon's anxiety and reluctance to proceed with any further biopsy. Ranjan et al (29) found no significant difference between the most experienced and other surgeons regarding negative biopsies. Two non-diagnostic cases were the 94 th and 125 th procedures in the present study.…”
Section: Diagnostic Yield and Accuracymentioning
confidence: 94%
“…There are few studies on the management and follow up of non-diagnostic biopsy cases in the literature (1,13,23,29,39). The institution of empirical treatments after a presumptive diagnosis using serial imaging was advised for patients with non-diagnostic biopsies (1,39).…”
Section: Management and Follow-up Of Non-diagnostic Casesmentioning
confidence: 99%
“…Additionally, heterogeneity often requires multiple sampling, which is potentially dangerous in the brainstem. 16 Even in the most recent study by Kesari et al,7 published in 2008 and involving a large series, a histological diagnosis was obtained in only 53% of the patients. Many authors claim a very restrictive indication for radiologically unclear lesions due to the presumed high-risk profile.…”
Section: Histological Results and Complicationsmentioning
confidence: 99%
“…4c), a higher rate of specimens being located in areas with neuroradiologically confirmed contrast medium uptake was related to an increasing number of conclusive diagnoses for MGMT promoter methylation status. Since the computed tomography era it is well known that stereotactic biopsies of intracerebral lesions are most likely to yield a histopathological diagnosis if the contrast-enhanced portion of the lesion is targeted in preference to the necrotic part [30,31,32,33]. On the other hand, targeting contrast-enhanced tissues only might decrease diagnostic accuracy [30].…”
Section: Discussionmentioning
confidence: 99%